The success rate of 2619 consecutively inserted extra-alveolar miniscrews for temporary skeletal anchorage - soroush basafa; Johnny Liaw; Nikhilesh Vaid; Donald Ferguson (Journal of Dental Materials and Techniques)
Objective: Temporary anchorage devices (TADs) have become integral in orthodontic treatments due to their ability to provide skeletal anchorage. This study aimed to evaluate the success rates of extra-alveolar miniscrews as a function of patient gender, placement location, and miniscrew size.Methods: This retrospective cross-sectional study analyzed the dental records of 744 patients treated with TADs from 2016 to 2018. A total of 2,619 miniscrews of three different sizes (2×12 mm, 2×10 mm, and 1.4×8 mm) were inserted in five locations: the palate, mandibular buccal shelf, infrazygomatic crest, anterior maxilla, and anterior mandible. Success was defined as stability throughout treatment, while TADs that had to be removed, replaced or repositioned were regarded as failures. Statistical analyses included chi-square, ANOVA, and post hoc Tukey’s tests. P-value<0.05 was considered statistically significant.Results: The overall success rate was 79.3%. There was a significant association between the area of miniscrew insertion and TAD success rate (P<0.001). The highest success rate was observed in the palate (97.1%), followed by the mandibular buccal shelf (94.4%). The lowest success rate was observed in the infrazygomatic crest (73.8%). The 2×10 mm miniscrew size showed the highest success rate (87.6%), whereas 2×12 mm exhibited the lowest (75.4%).Conclusions: Miniscrew success was significantly affected by the placement area, and the screw length and size. Palate and mandibular buccal shelf sites provided superior stability, and the 2×10 mm miniscrews provided the most successful results. These findings can aid orthodontists in TAD selection and treatment planning to achieve optimum outcomes